2012
DOI: 10.1371/journal.pone.0044968
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA-Mediated Gene Expression Regulation in the Pathological Development of Stem Canker Disease in Populus trichocarpa

Abstract: MicroRNAs (miRNAs), a type of short (21–23 nucleotides), non-coding RNA molecule, mediate repressive gene regulation through RNA silencing at the post-transcriptional level, and play an important role in defense and response to abiotic and biotic stresses. In the present study, Affymetrix® miRNA Array, real-time quantitative PCR (qPCR) for miRNAs and their targets, and miRNA promoter analysis were used to validate the gene expression patterns of miRNAs in Populus trichocarpa plantlets induced with the poplar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 67 publications
7
87
3
Order By: Relevance
“…reported from a previous study were also found in our research (Zhao et al 2012a, b). In plants, a majority of miRNAs are mainly derived from intergenic regions, and a minority of miRNAs is derived from introns or exons (Teune and Steger 2010).…”
Section: Identification and Analysis Of Novel Mirnas Elicited By M Osupporting
confidence: 90%
See 1 more Smart Citation
“…reported from a previous study were also found in our research (Zhao et al 2012a, b). In plants, a majority of miRNAs are mainly derived from intergenic regions, and a minority of miRNAs is derived from introns or exons (Teune and Steger 2010).…”
Section: Identification and Analysis Of Novel Mirnas Elicited By M Osupporting
confidence: 90%
“…They are a group of endogenous, non-coding sRNAs involved in regulating gene expression mainly via repressing the translation or mediating the cleavage of target mRNA at the post-transcriptional level (Campo et al 2013). In addition to their role in regulating gene expression associated with various plant developmental processes, such as organ morphogenesis, signal transduction pathway, responses to environmental stresses (Lu et al 2007), miRNAs have also emerged as a potentially important means to be applied in the studies on the complex regulatory networks being operated during plantfungus interactions (Jones-Rhoades and Bartel 2004; Nunes et al 2011;Zhao et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%
“…We then compared all of these putative miRNAs to gain insight into their evolutionary relationship and to enlighten whether these miRNA genes are conserved between the organisms. The miRNA families (miR156, miR159, miR160, miR164, miR166, miR172, miR319, miR398, and miR408) from the previous studies (Gupta et al 2014;Zhao et al 2012) that we also predicted in our study should be analyzed under EFB disease conditions to elucidate whether they have some roles on defense mechanisms or not, and how they are regulated in the plant cell primarily. The other predicted putative miRNAs of hazelnut should also be taken into account in further studies since they may play other important roles on different plant mechanisms and they may be transferred to other accessions through breeding approaches.…”
Section: Resultsmentioning
confidence: 71%
“…Although no direct relationship has been found yet between microRNA and Jefferson's EFB resistance, it is still a question whether those putative microRNAs predicted in our study have key regulatory roles on this mechanism. Moreover, recent studies have pointed out that miRNA machinery is involved in regulating the plant defense system against some fungal pathogenesis (Gupta et al 2014;Zhao et al 2012). In one of the study, regulation of some miRNA families from P. trichocarpa including miR1448 , miR1450, miR156, miR159, miR160, miR164, miR166, miR168, miR172, miR319, miR398, miR408, and their targets in response to fungal infection were reported (Zhao et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation